The Effect of Financial Distress, Leverage, and Inventory Intensity on Tax Avoidance in Primary Consumer Goods Sector Companies - Hapsari Inawati Susanto; Yuniarwati Yuniarwati (Dinasti Accounting Review, 2026)
This study aims to analyze the effect of financial distress, leverage, and inventory intensity on tax avoidance, with the research object being primary consumer goods sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2021–2024, totaling 132 companies. The sample was selected using a purposive sampling technique, resulting in 103 companies. The analysis method used is multiple linear regression with the EViews application. The results of the study indicate that financial distress and inventory intensity do not have a significant effect on tax avoidance, while leverage has a positive and significant effect on tax avoidance. Simultaneously, financial distress, leverage, and inventory intensity have an effect on tax avoidance; however, the influence is relatively weak. The implication of this study is that in evaluating a company, one should not only consider financial aspects but also its compliance with legal regulations.